2018
DOI: 10.5194/acp-18-13429-2018
|View full text |Cite
|
Sign up to set email alerts
|

Composition and mixing state of atmospheric aerosols determined by electron microscopy: method development and application to aged Saharan dust deposition in the Caribbean boundary layer

Abstract: Abstract. The microphysical properties, composition and mixing state of mineral dust, sea salt and secondary compounds were measured by active and passive aerosol sampling, followed by electron microscopy and X-ray fluorescence in the Caribbean marine boundary layer. Measurements were carried out at Ragged Point, Barbados during June–July 2013 and August 2016. Techniques are presented and evaluated, which allow for statements on atmospheric aerosol concentrations and aerosol mixing state based on collected sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 112 publications
(135 reference statements)
4
58
2
Order By: Relevance
“…For instance, the mean real part of the refractive index (440 nm) during SALTRACE retrieved with sun photometer data is 1.47 for mineral dust (Table 2), which is much lower than the value reported from in situ observations, about 1.55-1.61 . The problems encountered to retrieve the correct dust refractive index using a spheroid model were also highlighted by Kemppinen et al (2015). Conversely, the single-scattering albedo and its spectral dependence (Table 2) are very similar for dust using sun photometer and in situ optical instruments.…”
Section: Comparison With In Situ Observations At Ragged Pointmentioning
confidence: 97%
“…For instance, the mean real part of the refractive index (440 nm) during SALTRACE retrieved with sun photometer data is 1.47 for mineral dust (Table 2), which is much lower than the value reported from in situ observations, about 1.55-1.61 . The problems encountered to retrieve the correct dust refractive index using a spheroid model were also highlighted by Kemppinen et al (2015). Conversely, the single-scattering albedo and its spectral dependence (Table 2) are very similar for dust using sun photometer and in situ optical instruments.…”
Section: Comparison With In Situ Observations At Ragged Pointmentioning
confidence: 97%
“…Feldspar and K-feldspar indices are defined (Appendix A), showing the similarity of the measured particle composition to a feldspar composition. As it was found that index values >0.8 identify a feldspar particle with high probability [42], this threshold value is used here to assess the contribution of feldspar particles to the total deposition. Note that for example a layer of clay minerals covering a feldspar grain might therefore prohibit the classification as (pure) feldspar.…”
Section: Class Name Conditions For Being Positively Classifiedmentioning
confidence: 99%
“…However, these are usually trace to minor species [31,53]. As an estimate for Ca atmospheric processing, single particle apparent relative ion balances can be defined [42]. Here, we use the Ca-Mg-S relative ion balance, defined as…”
Section: Class Name Conditions For Being Positively Classifiedmentioning
confidence: 99%
See 2 more Smart Citations